Pengaruh Kualitas Informasi, Kualitas Sistem, Dan Kualitas Layanan Terhadapp Kepuasan Pengguna E-Commerce Situs Shopee (Studi Kasus Mahasiswa Manajemen Angkatan 2019 Unisma) - Diana Putri Milenia; Nurhajati Nurhajati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine how much influence the quality of information, system quality, and service quality has on the satisfaction of Shopee site users. The population in this study was among 598 Management students from the 2019 Faculty of Economics and Business, with a total sample of 86 respondents. This study uses data collected through questionnaires using a Likert scale measurement. This study uses multiple linear regression analysis with the results obtained that the quality of information, quality systems, and services together influence user satisfaction. The quality of information partially influences user satisfaction, while the quality of systems and services partially does not influence user satisfaction. This is based on many users submitting opinions through reviews on PlayStore. Keywords : Information Quality, System Quality, Service Quality, User Satisfaction.